An Evaluation of the Work and Life Conditions and the Quality of Life in 60 to 65 Year-Old White-Collar Employees, Manual Workers, and Unemployed Controls. Issue 5 (May 2017) - Sołtysik, Bartłomiej K.; Kroc, Łukasz; Pigłowska, Małgorzata; Guligowska, Agnieszka; Śmigielski, Janusz; Kostka, Tomasz
Abstract : Objectives: Assessment of the work and life conditions of 60 to 65-year-old seniors with regard to type of work and quality of life (QoL). Methods: The European Foundation for Improvement of Living and Working Conditions Questionnaire and the EuroQol 5D were used to evaluate work and life conditions and QoL in the three age- and sex-matched 60 to 65-year-old groups (white-collar, manual workers, and unemployed subjects, 100 each group, 50% of women). Results: Manual workers and unemployed subjects had lower QoL score (0 to 100 point scale) than white-collar workers (accordingly 72.2; 71.2; 76.2; P < 0.05). In working subjects ( n = 200), QoL was inversely associated with reported health problems ( P < 0.01) and directly related to quality of work ( P < 0.001). In the group of manual workers ( n = 100), QoL indices were influenced by health factors and quality of work, while in the intellectual group ( n = 100) mainly by health factors. Conclusions: Quality of work and health assessment are the main domains that influence older workers' QoL and may contribute to the shortening of the work period and accelerated transfer to retirement. Quality of work assessment seems especially important in older manual workers.